Watercress ebook - Wang, Andrea (2021)
Caldecott Medal Winner Newbery Honor Book APALA Award Winner A story about the power of sharing memories—including the painful ones—and the way our heritage stays with and shapes us, even when we don’t see it.  New England Book Award Winner A New York Times Best Children’s Book of the Year A Boston Globe-Horn Book Honor Book While driving through Ohio in an old Pontiac, a young girl's Chinese immigrant parents spot watercress growing wild in a ditch by the side of the road.  They stop the car, grabbing rusty scissors and an old paper bag, and the whole family wades into the mud to gather as much as they can.  At first, she's embarrassed. Why can't her family just get food from the grocery store, like everyone else? But when her mother shares a bittersweet story of her family history in China, the girl learns to appreciate the fresh food they foraged—and the memories left behind in pursuit of a new life. Together, they make a new memory of watercress. Author Andrea Wang calls this moving, autobiographical story “both an apology and a love letter to my parents.”  It’s a bittersweet, delicate look at how sharing the difficult parts of our histories can create powerful new moments of family history, and help connect us to our roots.  Jason Chin’s illustrations move between China and the American Midwest and were created with a mixture of traditional Chinese brushes and western media. The dreamy, nostalgic color palette brings this beautiful story to life.  An endnote from the author describes her personal connection to the story, and an illustrator’s note touches on both the process of the painting, and the emotional meaning brought to the work.  New England Book Award Winner A New York Times Best Children’s Book of the Year A Wall Street Journal Best Children's Book of the Year A Boston Globe Best Children's Book of the Year A Washington Post Best Children's Book of the Year A Boston Globe-Horn Book Honor Book Winner of the Cybils Award An SCBWI Crystal Kite Award Winner A New York Public Library Best Book of the Year A Chicago Public Library Best Book of the Year An ALSC Notable Children's Book Named a best book of the year by Publishers Weekly, BookPage, School Library Journal, Kirkus Reviews, Publishers Lunch, Shelf Awareness , and more! A CBC/NCSS Notable Social Studies Trade Book An NPR 'Book We Love!' A Junior Library Guild Gold Standard Selection!